2016
DOI: 10.1158/1055-9965.epi-16-0556
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Levels of Estrogens and PGE2 Synthesis in Relation to Postmenopausal Breast Cancer Risk

Abstract: Background Prostaglandin E2 (PGE2) induces aromatase expression in adipose tissue leading to increased estrogen production that may promote the development and progression of breast cancer. However, few studies have simultaneously investigated systemic levels of PGE2 and estrogen in relation to postmenopausal breast cancer risk. Methods Here we determined urinary estrogen metabolites (EMs) using mass spectrometry in a case-cohort study (295 incident breast cancer cases and 294 subcohort members), and using l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 43 publications
0
18
2
Order By: Relevance
“…In the current study, which was smaller than the previous studies and cross-sectional rather than prospective, PGE-M was not significantly higher in cases than in controls. We did find that higher BMI was associated with higher PGE-M as determined by LC/MS but not by EIA (Morris et al , 2013; Cui et al , 2014), and we did not replicate a reported correlation between urine PGE-M and urine oestrone (E1) levels (Kim et al , 2017).…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…In the current study, which was smaller than the previous studies and cross-sectional rather than prospective, PGE-M was not significantly higher in cases than in controls. We did find that higher BMI was associated with higher PGE-M as determined by LC/MS but not by EIA (Morris et al , 2013; Cui et al , 2014), and we did not replicate a reported correlation between urine PGE-M and urine oestrone (E1) levels (Kim et al , 2017).…”
Section: Discussioncontrasting
confidence: 74%
“…Consistent with this, elevated C-reactive protein in serum has been associated with increased risk for postmenopausal breast cancer, at least among overweight and obese women (Hong et al , 2013; Gunter et al , 2015). Extending this theme, a potential marker of inflammation, PGE-M, was reported to be modestly elevated prior to postmenopausal breast cancer diagnosis in three previous studies (Kim et al , 2013, 2017; Cui et al , 2014). In the current study, which was smaller than the previous studies and cross-sectional rather than prospective, PGE-M was not significantly higher in cases than in controls.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The regulation of COX-2 by BPA might be related to the interaction of COX-2 and estrogen. In various estrogen-dependent tumors including endometrial cancer and ovarian cancer, estrogen promotes the proliferation and invasion of cancer by upregulating COX-2 expression 34,35 . COX-2 is involved in the positive feedback regulation between estrogen and inflammatory factors, where COX-2/ mPGES-1 upregulates the expression of aromatase and increases the levels of estrogen, which in turn upregulates COX-2 expression via combination with the estrogen receptor 36 .…”
Section: Discussionmentioning
confidence: 99%
“…We were able to show that female MSC secrete signi cantly more PGE-2 in primed MSC-S than males. Research has indicated that sex hormones play roles in controlling the presence and function of PGE-2 and may work via a feedback loop in female adipose tissue [69,70], a possible mechanism responsible for the elevated PGE-2 response to in ammatory stimuli in fMSC and subsequent immune regulation.…”
Section: Discussionmentioning
confidence: 99%